BRAND AWARENESS DAN GAYA HIDUP DALAM MEMPENGARUHI KEPUTUSAN PEMBELIAN IPHONE PADA MAHASISWA - Heru Totok Tri Wahono (STIE PGRI Dewantara Jombang, 2026)
This study aims to analyze the influence of Brand Awareness and Lifestyle on the Purchase Decision of iPhone Smartphones among students of the Economic Education Study Program, Faculty of Teacher Training and Education, PGRI Jombang University. Purchasing decisions for premium smartphones in the student environment are strongly influenced by brand image and social tendencies. This quantitative research employed a survey method, using the entire student population from the 2021-2024 cohorts as the sample (Total Sampling), with data collected via Google Form questionnaires. Data analysis included classic assumption tests (Normality, Multicollinearity, Heteroscedasticity) and Multiple Linear Regression, alongside hypothesis testing (t-Test, F-Test, and Coefficient of Determination R 2) using SPSS 22. The results indicate that (1) Brand Awareness has a positive and significant influence on the purchase decision (Sig.=0.004<0.05). (2) Lifestyle also has a positive and significant influence on the purchase decision (Sig.=0.000<0.05). The simultaneous contribution of Brand Awareness and Lifestyle accounts for 63.2% of the variance in the purchase decision, while the remaining 36.8% is influenced by other variables not examined in this study.